Estimativa da evapotranspiração de referência para duas localidades do Nordeste através de oito métodos, utilizando o programa REF-ET - Medeiros, Almiro Tavares (1996)
The software REF-ET release 2.1 was applied to estimate the reference evapotranspiration (ETo in Pentecoste-CE and Mossoró-RN). In Pentecoste datum were collected from the Fazenda Experimental Vale do Curu's weather station (set of datum from 1966 to 1986, from 1974 to 1978, and for 1977 and 1979), and in Mossoró from the ESAM weather station (set of datum from 1970 to 1982). The set of datum of 1977 and 1979 was used as representative of a dried and rained year, respectively. In all simulations, alfalfa was used as a reference crop. Using the software, the ETo was calculated through the following methodologies: Penman Kimberly 1982, FAO-Penman 1973, Penman 1968, Hargreaves 1985, FAO-Radiation, FAO-Blaney Criddle, Class .A. Pan, and Penman-Montheith, that was used as the standard for evaluating the other approaches. The results show that, in the monthly analyses at both sites, the FAO-Penman method best estimate the Penman-Monteith ETo values. However, in the diary analyses, the result depends on the month analyzed. Thus, the Penman Kimberly 1982 from March to November, the FAO-Blaney CriddJe in January and February, and FAO-Penman in December appear to best approach the Penman-Monteith ETo values. It was even verified that the Penman 1963, Hargreaves 1985, and FAO Radiantion methods produces acceptable values for ETo. In general, however, the Class .A. Pan approach results in the highest deviation of ETo values. It was also verified that the FAO-Penman approach tends to overestimate the ETo.